Windows 7 for beginners - Northrup, Anthony; Safari eBooks ([S.l.] : InfiniteSkills, 2010)
"This Microsoft Windows 7 Tutorial Video is narrated by long time author and expert trainer Tony Northup. Covering over 7 hours this training video takes an in-depth look at Microsoft's latest operating system, Windows 7. Starting with the basics of installation, Tony guides you through the setup, and use of the most important features of Windows 7. Tony covers topics such as the taskbar, notification area, creating and navigating folders, Internet Explorer 8, Media Player, and much more, making this a completely comprehensive look at the most exciting Microsoft operating system to date. By the conclusion of this video based training course, you will be capable of installing, customizing and using this operating system with confidence, the self-paced nature of this tutorial allows users of all levels to quickly learn Windows 7 no matter what their prior experience"--Resource description page.
Title from resource description page (viewed July 19, 2011).
Presenter, Tony Northrup.
Keywords: Microsoft Windows (Computer file); Operating systems (Computers); Electronic books